Gas Chromatography/Mass Spectrometry Analysis of Essential Oil From Different Vegetative Organs and Fruits of Foeniculum vulgare Mill. var. vulgare Growing in Turkey - COSGE, BELGIN; IPEK, ARIF; GURBUZ, BILAL (Asian Journal of Chemistry, 2010)
The essential oils obtained by hydrodistillation of fruit, stem, leaf stalk and leaf of bitter fennel (Foeniculum vulgare Miller, Apiaceae) were analyzed by GC-MS. Essential oil content was obtained 7.25 % in fruit, 0.375 % in stem, 0.857 % in leaf stalk and 0.75 % in leaf. trans- Anethole was the major component in the fruit (75.05 %), stem (64.09 %) and leaf stalk (75.64%) and the leaf oil which contained α-phellandrene (38.23%) and α-pinene (31.79%) as the main components. The chemical composition of the essential oils investigated was found both quantitatively and qualitatively different.